Whittaker asymptotics of shell-model wave functions for excited states of 13C (Physical Sciences and Technology, 2018)
Halo and skin structure of 1/2+, 3/2+, 5/2+ excited states of 13C nucleus is under investigation. The modified radialfunctions have been constructed basing on the shell model functions. The matching procedure was performedwhile using the corresponding Whittaker exponential-like asymptotics. To find the matching radius via theoscillator parameter r0 three options were examined related to the experimental and theoretical data on the meansquare radii, and uncertainty relation. The renormalization of the modified functions shows the input of theasymptotic region near 15-20%. The most qualitative effect is the redistribution of the probability density bothat short and long-range distances. The obtained functions are given as parametrization by Gauss basis. It isproposed to confirm the observed halo and skin states of 13C via the impulse distributions measured with differentprobing projectile like high-energy protons or α-particles. The most probable halo effect the 2S-state reveals dueto the node behavior of the corresponding radial wave function.